NZ J Ecol 2018
DOI: 10.20417/nzjecol.42.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the population trend and threats to New Zealand’s Fiordland crested penguin using counting and demographic modelling approaches

Abstract: The Fiordland crested penguin Eudyptes pachyrhynchus is one of the least studied crested penguin species, with indications the species has a declining population, which would be in line with the historic and contemporary trends for most crested penguins. To determine the current population trend of the Fiordland crested penguin, a number of monitoring programmes using both abundance counts and demographic modelling approaches were carried out between 1990 and 2010 in the northern half of the species' range. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…For example, climate change is a global issue, not influenced by political boundaries, that requires intergovernmental effort at a global scale, whilst limiting coastal development and regulating marine-capture fisheries continues to be a growing challenge as 250 additional humans are born every minute (The World Factbook, 2016). With such pressures, one of the critical challenges facing ecologists is the attribution of cause through analyzing long-term data that describe changes in functional traits (e.g., body condition, foraging activity), vital rates (e.g., survival, fecundity) and population size (Jenouvrier et al, 2018;Otley et al, 2018). Few studies have accounted for the effects of stressors, such as climate change, on the complete life cycle of species, thereby accounting for multiple seasonal and carry-over effects of the stressor (Jenouvrier et al, 2012;Iles and Jenouvrier, 2019).…”
Section: Proactive Managementmentioning
confidence: 99%
“…For example, climate change is a global issue, not influenced by political boundaries, that requires intergovernmental effort at a global scale, whilst limiting coastal development and regulating marine-capture fisheries continues to be a growing challenge as 250 additional humans are born every minute (The World Factbook, 2016). With such pressures, one of the critical challenges facing ecologists is the attribution of cause through analyzing long-term data that describe changes in functional traits (e.g., body condition, foraging activity), vital rates (e.g., survival, fecundity) and population size (Jenouvrier et al, 2018;Otley et al, 2018). Few studies have accounted for the effects of stressors, such as climate change, on the complete life cycle of species, thereby accounting for multiple seasonal and carry-over effects of the stressor (Jenouvrier et al, 2012;Iles and Jenouvrier, 2019).…”
Section: Proactive Managementmentioning
confidence: 99%
“…Several studies have demonstrated major declines in crested penguins during the late 20th century (Crawford et al, 2009(Crawford et al, , 2010Davis 2013;Morrison et al, 2015;Otley et al, 2018). Taylor (2000) and Otley et al (2018) suggest E. pachyrhynchus populations have declined significantly since this time. Surveys of E. sclateri suggest that populations were stable until 2011, but have subsequently declined by 19% (Hiscock and Chilvers, 2014).…”
Section: Introductionmentioning
confidence: 99%